SOSIALISASI PENGEMBANGAN PRODUK UMBUT BATANG PISANG DI NAGARI TANJUNG PONDOK TAPAN KEC. BASA AMPEK BALAI - Yanti, Novita Rahma; M. Nurzen, M. Nurzen; Daflaini, Daflaini (Institut Agama Islam Negeri Kerinci, 2022)
This research aims to provide a clear understanding of how entrepreneurial management can be applied in a real setting. And it is hoped that readers can gain insight into effective management strategies in organizing and directing entrepreneurship to achieve the desired goals. This research uses an interdisciplinary and cross-sector approach. The results of this research show that people in the Tanjung Pondok Tapan village do not know the benefits of banana unbut, where banana unbut can actually be processed into a product that can be bought and sold and can even become a typical food from the Tanjung Pondok Tapan village.